THE EFFECT OF TOTAL ASSET TURNOVER, NET PROFIT MARGIN, AND DEBT TO EQUITY RATIO ON PROFIT GROWTH IN AUTOMOTIVE COMPANIES LISTED IN INDONESIA STOCK EXCHANGE - Firman, Dody; Salvia, Salvia (CV. Radja Publika, 2021)
This study aims to determine whether total asset turnover, net profit margin, and debt to equity ratio have an effect either partially or simultaneously on profit growth in automotive companies listed on the Indonesia Stock Exchange. The approach used in this study is an associative approach. The population used in this study were 13 companies and a sample that met the criteria (purposive sampling) was 7 companies. Data collection techniques used in this study using documentation techniques and data sources used in this study are secondary data sources. The data analysis technique used in this study is a quantitative technique with multiple linear regression analysis, hypothesis testing and coefficient of determination test. Data management using SPSS (Statistical Package For The Social Sciences) version 20 for windows. The results of this study are partially total asset turnover has no effect on profit growth. Partially, net profit margin has no effect on profit growth. Partially the debt to equity ratio has an effect on profit growth. Simultaneously total asset turnover, net profit margin, and debt to equity affect profit growth in automotive companies listed on the Indonesia Stock Exchange for the 2014-2018 period. Partially the debt to equity ratio has an effect on profit growth. Simultaneously total asset turnover, net profit margin, and debt to equity affect profit growth in automotive companies listed on the Indonesia Stock Exchange for the 2014-2018 period. Partially the debt to equity ratio has an effect on profit growth. Simultaneously total asset turnover, net profit margin, and debt to equity affect profit growth in automotive companies listed on the Indonesia Stock Exchange for the 2014-2018 period.